Springback prediction of multiple reciprocating bending based on different hardening models. (April 2022) - Meng, Qingdang; Zhao, Jun; Mu, Zhenkai; Zhai, Ruixue; Yu, Gaochao
Abstract: The metal forming process often involves multiple reciprocating bending springback problems. The springback prediction of reciprocating bending is more difficult than that of single bending. Based on the isotropic hardening model, the kinematic hardening model, the mixed hardening model and the YU model, the effects of different hardening models, variable elastic modulus and bending times on the springback are studied. An experimental method for measuring the springback of multiple reciprocating bending is adopted. The multiple reciprocating pure bending is realized by arc-shaped punch and die. The results show that different hardening models have good predictions for the springback of the first bending. However, as the number of bending increases, compared with the increasing error value of other hardening models, only the YU model that considers the variable elastic modulus can realize the accurate prediction of springback, and the error of springback results is within 5% for each bending. The research work is a basic research on the springback problem of multiple reciprocating bending, which can improve the simulation accuracy of metal forming processes involved in this problem, especially for the roller straightening and setting round process with more reciprocating bending.